A method for reusing cement-based materials after groundwater remediation in the field of electromagnetic shielding
By preparing cement-based materials containing ferrite magnetic powder and purifying them in heavy metal-contaminated groundwater, the materials are used as electromagnetic shielding materials, which solves the problem of recycling cement-based materials, improves the electromagnetic shielding effect and maintains good mechanical properties.
Patent Information
- Application Number
- CN202410744978.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2044-06-11
AI Technical Summary
Existing cement-based materials cannot be effectively reused after groundwater remediation, and their service life as PRB materials is short, resulting in resource waste and environmental pollution.
A cement-based material is prepared by mixing silica-alumina materials, aggregates and ferrite magnetic powder, adding additives, and then used as an electromagnetic shielding material after purification in groundwater containing heavy metal ions. The electromagnetic shielding performance is improved by utilizing the adsorption and solidification of heavy metal ions in the cement-based material.
It realizes the reuse of cement-based materials, improves their performance in the field of electromagnetic shielding, solves the problems of resource waste and environmental pollution, and maintains good mechanical properties.
Smart Images

Figure SMS_1 
Figure HDA0004886136840000011 
Figure HDA0004886136840000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of material engineering and electromagnetic shielding technology, and particularly relates to a method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding. Background Art
[0002] With the continuous development of urbanization in recent years, heavy metal ion pollution has appeared in the groundwater systems around cities and factories. Permeable reactive barrier (PRB) in situ technology is currently an important technology for contaminated groundwater treatment, and the use of cement-based materials in PRB materials has gradually become a major research direction.
[0003] The surface of cement-based materials contains numerous adsorption sites, which can adsorb and solidify heavy metal ions in groundwater, thereby remediating contaminated groundwater. Compared to conventional adsorbents (such as zeolite and activated carbon), cement-based materials offer advantages such as low cost, readily available raw materials, and easy maintenance. However, as PRB materials, cement-based materials also have some disadvantages, including a relatively short service life. Cement-based materials used as PRB materials lose most of their adsorption capacity after 2–3 years of burial, whereas other in-situ groundwater remediation agents have a longer service life of approximately 10 years. When cement-based materials lose their ability to remediate groundwater, they must be removed from the ground and replaced with new ones. Disposal options for removed cement-based materials primarily include crushing and reuse or stockpiling. However, due to the large amount of contaminants solidified within them, reuse options are limited. Large-scale stockpiling would occupy large areas of land and pollute the surrounding environment. Therefore, the reuse of large quantities of cement-based materials used for groundwater remediation has become a pressing issue, and it is necessary to find ways to reuse permeable concrete used for groundwater remediation.
[0004] Current research on electromagnetic shielding technology for cement-based materials primarily focuses on reinforced concrete and concrete with conductive fillers. However, the addition of conductive fillers to concrete can also present challenges. For one thing, the high amount of conductive fillers used leads to poor mechanical properties. Furthermore, the high cost of some conductive fillers limits their application. Therefore, certain characteristics of cement-based materials used for groundwater remediation make them suitable for electromagnetic shielding applications. For example, the large amounts of heavy metal ions adsorbed, adhered, and solidified within them can serve as conductive fillers. Furthermore, driven by carbon reduction policies, the use of industrial solid waste in the preparation of cement-based materials is increasing. The inclusion of solid waste can enhance the adsorption capacity of cement-based materials for heavy metal ions. Furthermore, the high Fe₂O₃ content in solid waste can enhance the application of cement-based materials in electromagnetic shielding. The water purification function of cement-based materials is closely related to their pore surface area. Therefore, the incorporation of extremely fine-particle materials can significantly enhance their adsorption capacity for heavy metal ions. Magnetic powder has an extremely fine particle size (less than 0.6mm). Adding it to cement-based materials can improve their adsorption of heavy metal ions. Furthermore, the main component of magnetic powder, Fe2O3, can enhance the electromagnetic shielding properties of cement-based materials. Therefore, if permeable concrete used for groundwater remediation can be used in the electromagnetic shielding field of cement-based materials, it will not affect the mechanical properties of the cement-based materials while providing a certain electromagnetic shielding effect, which is a good recycling method. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to solve the problem that cement-based materials used for groundwater remediation cannot be effectively reused after use, and to provide a method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding. The cement-based material prepared by the method provided by the present invention can be used for groundwater remediation, and can be used as electromagnetic shielding material after use and recycling, and has excellent electromagnetic shielding effect.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] A method for recycling cement-based materials after groundwater remediation in the field of electromagnetic shielding, comprising the following steps:
[0008] S1. Mixing and stirring the silica-alumina material, aggregate, and ferrite magnetic powder for 30 seconds to 1 minute, adding an additive, and continuing stirring for 30 seconds to 1 minute to obtain a mixture. The mixture is placed in a mold, compacted, and sealed. The mold is removed after 1 day, and then cured under standard curing conditions for 28 days to obtain a cement-based material.
[0009] S2. The cement-based material prepared in step S1 is buried around groundwater containing heavy metal ions, the groundwater is purified for 1-2 years, and then taken out and used as an electromagnetic shielding material.
[0010] In the above scheme, in step S1, the silicon-aluminum material is 100 parts, the aggregate is 150-640 parts, the ferrite magnetic powder is 2-10 parts, and the additive is 20-85 parts.
[0011] In the above solution, the silicon-aluminum material includes: 70-80 wt% of conventional silicon-aluminum raw material and 20-30 wt% of silicon-aluminum raw material with high iron oxide content.
[0012] In the above scheme, the conventional siliceous alumina raw materials are one or more of cement, mineral powder, silica fume, and metakaolin; the siliceous alumina raw materials with high iron oxide content are one or more of steel slag, iron tailings, red mud, and coal gasification slag.
[0013] In the above solution, the ferrite magnetic powder is mainly composed of iron oxide or ferroferric oxide, with a purity greater than 99.9% and a particle size of 0.06 to 0.6 mm.
[0014] In the above solution, the aggregate is one or more of crushed stone, recycled brick-concrete material, and high-strength ceramsite.
[0015] In the above scheme, the auxiliary agent is water or an alkaline activator; when the silicoaluminous raw material contains one or more of mineral powder, high-alkaline ore, and steel slag, the auxiliary agent is an alkaline activator.
[0016] Furthermore, the preparation method of the alkaline activator is: adding alkali to water, stirring and dissolving, then adding silicate thereto, and continuing stirring for 30 seconds to 2 minutes to prepare the alkaline activator; wherein the mass ratio of alkali, water, and silicate is 1: (3 to 4): (1.5 to 2.5); the alkali is one of sodium hydroxide and potassium hydroxide or a mixture; the silicate is one of sodium silicate and potassium silicate or a mixture.
[0017] The cement-based material is prepared by the above-mentioned method of recycling cement-based materials after groundwater remediation in the field of electromagnetic shielding.
[0018] The present invention also provides a conductive silver tape for fixing the cement-based material test blocks together. According to different electromagnetic shielding usage environments, multiple cement-based material test blocks can be adhered to each other to improve the conductive continuity between the test blocks.
[0019] The present invention also provides a perforated pulling device for stacking the prepared cement-based material test blocks and burying them underground. The perforated pulling device has a bottom length of 10 to 70 meters, a width of 0.3 to 1 meter, a depth of 4 to 10 meters, and a thickness of more than 15 mm. The specific size of the perforated pulling device mainly depends on the application environment of the PRB material and the actual underground space. There are several holes on the perforated pulling device, with a hole diameter of 1 to 10 cm and a hole spacing of 10 to 50 cm. The holes can form underground runoff. The perforated pulling device has corrosion resistance, water erosion resistance, and a certain load-bearing capacity. The material is stainless steel plate or a thicker acrylic plate.
[0020] The cement-based material is used as a material for making electromagnetic shielding room walls, shielding doors or shielding boxes after being used for groundwater remediation.
[0021] Regarding the current state of applications in the field of electromagnetic shielding, cement-based materials have two main disadvantages: First, the internal structure of cement-based materials is very dense, which is not conducive to the reflection of electromagnetic waves within them. The cement-based material provided by the present invention has a relatively large porosity of approximately 15% to 30%, which is beneficial to the absorption loss and internal reflection loss of electromagnetic waves in the cement-based material, thereby improving the electromagnetic shielding effect; second, the main components of the cement-based material have no shielding effect on electromagnetic waves, that is, they lack sufficient conductive fillers. The cement-based material provided by the present invention improves the electromagnetic shielding effect in two ways. First, during the groundwater remediation process, the cement-based material will adsorb and fix pollutants such as heavy metal ions on the adsorption sites of the cement-based material slurry and internal aggregates. In a highly alkaline environment, heavy metal ion precipitation will be generated and then distributed in the pores of the cement-based material, which will act as a conductive filler. This will further utilize the cement-based material after groundwater remediation and solve the storage problem. The second is to add ferrite magnetic powder with excellent conductivity into cement-based materials as an external dopant to improve the conductivity of the material itself. Furthermore, the particle size of ferrite magnetic powder is 1-60 microns, and the specific surface area is large, which is beneficial to improving the adsorption capacity of cement-based materials and absorbing more heavy metal ions on the surface of its slurry to improve conductivity.
[0022] Compared with the existing technology, the beneficial effects of the present invention are:
[0023] (1) The present invention provides a method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding. The cement-based materials prepared by this method have good mechanical properties and can be used as electromagnetic shielding materials after being used for groundwater remediation, and their electromagnetic shielding effect is excellent.
[0024] (2) The method provided by the present invention for recycling cement-based materials after groundwater remediation in the field of electromagnetic shielding can absorb a large amount of cement-based materials after groundwater remediation, and is a good way to reuse cement-based materials used for groundwater remediation.
[0025] Figures in the specification
[0026] Figure 1 This is a schematic diagram of a hole-lifting device provided by the present invention.
[0027] Figure 2 These are pictures of the cement-based material prepared in Example 2 of the present invention before and after being used for groundwater remediation.
[0028] Figure 3 This is a cross-sectional morphology of the cement-based material prepared in Example 3 of the present invention before and after being used for groundwater remediation. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] A method for recycling cement-based materials after groundwater remediation in the field of electromagnetic shielding, comprising the following steps:
[0031] S1. Mixing and stirring the silica-alumina material, aggregate, and ferrite magnetic powder for 30 seconds to 1 minute, adding an additive, and continuing stirring for 30 seconds to 1 minute to obtain a mixture. The mixture is placed in a mold, compacted, and sealed. The mold is removed after 1 day, and then cured under standard curing conditions for 28 days to obtain a cement-based material.
[0032] S2. The cement-based material prepared in step S1 is buried around groundwater containing heavy metal ions, the groundwater is purified for 1-2 years, and then taken out and used as an electromagnetic shielding material.
[0033] Wherein, in step S1, by mass, 100 parts of silicon-aluminum material, 150-640 parts of aggregate, 2-10 parts of ferrite magnetic powder, and 20-85 parts of additive are prepared.
[0034] The silica-alumina materials include: 70-80wt% conventional silica-alumina raw materials and 20-30wt% high-iron oxide content silica-alumina raw materials. Conventional silica-alumina raw materials include one or more of cement, mineral powder, silica fume, and metakaolin; high-iron oxide content silica-alumina raw materials include one or more of steel slag, iron ore tailings, red mud, and coal gasification slag. Ferrite magnetic powder is primarily composed of iron oxide or ferroferric oxide, with a purity greater than 99.9% and a particle size of 0.06-0.6mm. Aggregates include one or more of crushed stone, recycled brick-concrete materials, and high-strength ceramsite.
[0035] The auxiliary agent is water or an alkali activator. When the silicoaluminous raw material contains one or more of mineral powder, high-alkaline ore, and steel slag, the auxiliary agent is an alkali activator. The preparation method of the alkali activator is as follows: add alkali to water, stir to dissolve, then add silicate, and continue stirring for 30 seconds to 2 minutes to prepare the alkali activator. The mass ratio of alkali, water, and silicate is 1: (3-4): (1.5-2.5); the alkali is sodium hydroxide or potassium hydroxide, or a mixture thereof; the silicate is sodium silicate or potassium silicate, or a mixture thereof.
[0036] Example 1
[0037] First, add 40g of sodium hydroxide to 138.9g of water and stir to dissolve. Then add 80g of sodium silicate and stir for 1min to prepare an alkali activator, which is then sealed and stored. 1655g of crushed stone aggregate, 267g of mineral powder, 114g of steel slag powder, and 19.05g of iron oxide magnetic powder are placed in a horizontal mixing pot and stirred for 1min to uniformly mix. Then, the alkali activator is poured into the mixing pot and stirred for 2min. The freshly mixed concrete is then placed into a 100mm×100mm×100mm cubic test mold using the ramming method. The surface is immediately covered with plastic film. The mold is allowed to stand at room temperature for 24h before demolding. After demolding, the specimen is placed in a curing room with a relative humidity of ≥90% and continues to cure for 28d. The compressive strength of the cement-based material is tested at 28d. The mechanical properties are tested using a WAY-300 compressive strength testing machine.
[0038] Then, the prepared cement-based material test blocks were stacked on Figure 1 In the perforated lifting device shown, the perforated lifting device is buried underground, close to the wastewater plant with high heavy metal ion content, and intercepts and purifies groundwater within 20 meters of the surrounding factories for up to 2 years.
[0039] Two years later, the cement-based material samples buried underground were taken out through a hole-lifting device for compressive strength testing and electromagnetic shielding testing. The electromagnetic shielding performance test method was the coaxial cable transmission method.
[0040] The structural diagram of the hole-lifting device is as follows: Figure 1 The device is 20 meters long, 0.4 meters wide, and 5 meters deep, with a 50-centimeter hole diameter and 20-centimeter spacing. Made of stainless steel, it uses a conveyor belt to insert and remove cement-based materials.
[0041] The 28d compressive strength of the cement-based material in this embodiment is 35 MPa, the compressive strength after being used for groundwater remediation is 31.25 MPa, and the electromagnetic shielding performance at 1 GHz is 46.1 dB.
[0042] Example 2
[0043] First, 1077g of recycled brick aggregate, 243.6g of cement powder, 104.4g of iron tailings sand and 17.1g of iron oxide magnetic powder were put into a horizontal mixing pot and stirred in a mixer for 1min to make them evenly mixed. Then, 104.4g of water was poured into the mixing pot and stirred for 2min. The freshly mixed concrete was put into a 100mm×100mm×100mm cubic test mold by the tamping method, and the surface was immediately covered with plastic film. The test mold was allowed to stand at room temperature for 24h before demolding. After demolding, the specimen was placed in a curing room with a relative humidity of ≥90% and continued to be cured for 28d and the mechanical properties were tested.
[0044] Then, the prepared cement-based material test blocks were stacked on Figure 1 In the perforated lifting device shown, the device is buried underground near a wastewater treatment plant with a high content of heavy metal ions, and purifies groundwater for up to 2 years.
[0045] Two years later, the cement-based material samples buried underground were taken out using a hole-lifting device for compressive strength testing and electromagnetic shielding testing.
[0046] The 28d compressive strength of the cement-based material in this embodiment is 27 MPa, the compressive strength after being used for groundwater remediation is 24.39 MPa, and the electromagnetic shielding performance at 1 GHz is 54.5 dB.
[0047] Example 3
[0048] First, prepare the alkali activator. Add 36.83g of NaOH to a glass beaker containing 127.14g of water, stir to dissolve it, then add 73.8g of sodium silicate, and then seal it for later use. First, take 550g of high-strength ceramsite aggregate, 243.85g of cement powder, 105g of red mud powder and 13.9g of iron oxide magnetic powder and put them into a horizontal mixing pot. Add the alkali activator and stir it in a mixer for 1min to mix them evenly. Then pour the prepared alkali activator into the mixing pot and stir for 2min. Then, use the ramming method to put the freshly mixed concrete into a 100mm×100mm×100mm cubic test mold. Immediately cover the surface with plastic film. Let the test mold stand at room temperature for 24h before demolding. After demolding, place the specimen in a curing room with a relative humidity of ≥90% and continue curing for 28d before conducting mechanical property tests.
[0049] Then, the prepared cement-based material test blocks were stacked on Figure 1 In the perforated lifting device shown, the device is buried underground near a wastewater treatment plant with a high content of heavy metal ions, and purifies groundwater for up to 2 years.
[0050] Two years later, the cement-based material samples buried underground were taken out using a hole-lifting device for compressive strength testing and electromagnetic shielding testing.
[0051] The 28d compressive strength of the cement-based material in this embodiment is 20 MPa, the compressive strength after being used for groundwater remediation is 19.1 MPa, and the electromagnetic shielding performance at 1 GHz is 65.3 dB.
[0052] Comparative Example 1
[0053] The same preparation method as in Example 1 was used to prepare cement-based material samples, which were cured for 28 days and then subjected to mechanical property tests, and then directly subjected to electromagnetic shielding tests.
[0054] The 28d compressive strength of the cement-based material in this embodiment is 34.5 MPa, and the electromagnetic shielding performance at 1 GHz is 5.4 dB.
[0055] Comparative Example 2
[0056] The same preparation method as in Example 2 was used to prepare cement-based material samples, which were cured for 28 days and then subjected to mechanical property tests, and then directly subjected to electromagnetic shielding tests.
[0057] The 28d compressive strength of the cement-based material in this embodiment is 26 MPa, and the electromagnetic shielding performance at 1 GHz is 10.2 dB.
[0058] Comparative Example 3
[0059] The same preparation method as in Example 3 was used to prepare cement-based material samples, which were cured for 28 days and then subjected to mechanical property tests, and then directly subjected to electromagnetic shielding tests.
[0060] The 28d compressive strength of the cement-based material in this embodiment is 22 MPa, and the electromagnetic shielding performance at 1 GHz is 12 dB.
[0061] Comparative Example 4
[0062] This comparative example is a preparation of reinforced concrete. The mesh size is set to 200mm, the steel diameter D is set to 24mm or 40mm, and the concrete thickness P is equal to 100mm. Taking the mass of cement as 1, take 1 part of cement, 3.07 parts of fine aggregate and 3.10 parts of coarse aggregate and add them to the mixing pot. Stir for 1 minute, add 0.54 parts of water and continue stirring for 2 minutes. The freshly mixed concrete is placed in a 100mm×100mm×100mm cubic test mold, and the surface is immediately covered with plastic film. The test mold is left to stand at room temperature for 24 hours before demolding. After demolding, the specimen is placed in a curing room with a relative humidity of ≥90% and continues to cure for 28 days. Then, the concrete sample is placed in the steel bar matching unit for electromagnetic shielding performance testing.
[0063] In this embodiment, the electromagnetic shielding performance of reinforced concrete at 1 GHz is 53.2 dB.
[0064] Comparative Example 5
[0065] This comparative example is the preparation of a concrete material with conductive fillers. In terms of weight fraction, 20 parts of cement, 20 parts of fine aggregate, 20 parts of coarse aggregate, 5 parts of nickel fiber, and 3 parts of defoaming agent were taken and stirred in a mixer for 10 minutes. At the same time, 12 parts of colloidal graphite were added. A certain amount of water-soluble dispersant was added to the mixer and stirring was continued for 5 minutes. The freshly mixed concrete was placed in a 100mm×100mm×100mm cubic test mold. The mold was compacted at a speed of 90 seconds using a vibrator. The surface was immediately covered with plastic film. The mold was allowed to stand at room temperature for 24 hours before demolding. After demolding, the specimen was placed in a curing room with a relative humidity of ≥90% and continued to cure for 28 days. The electromagnetic shielding performance test was then carried out.
[0066] In this embodiment, the electromagnetic shielding performance of reinforced concrete at 1 GHz is 66.6 dB.
[0067] The performance of the cement-based material after groundwater remediation was compared with that of the cement-based material without groundwater remediation. The experimental results of Example 1 and Comparative Examples 1 to 3 are shown in Table 1.
[0068] Table 1 Performance data of Examples 1-3 and Comparative Examples 1-3
[0069]
[0070] From the test results in Table 1, it can be seen that, first, the 28d compressive strength of the cement-based material used for groundwater remediation is reduced by 4.5% to 10.7% compared to the cement-based material without groundwater remediation. However, the cement-based material after groundwater remediation still has good mechanical properties and meets the mechanical property requirements as an electromagnetic shielding material. Secondly, the electromagnetic shielding performance of ordinary cement-based materials is poor. The cement-based material for groundwater remediation proposed in the technical solution of the present invention has better electromagnetic shielding performance after being used for groundwater remediation. Therefore, there is a good prospect for further utilizing cement-based materials for groundwater remediation in the field of electromagnetic shielding. At the same time, it solves the problem of resource utilization of cement-based materials after groundwater remediation.
[0071] The cement-based materials after groundwater remediation were compared with concrete shielding materials (reinforced concrete and concrete with conductive fillers). The experimental results of Examples 1 to 3 and Comparative Examples 4 to 5 are shown in Table 2.
[0072] Table 2 Performance data of Examples 1-3 and Comparative Examples 4-5
[0073] Test items Example 1 Example 2 Example 3 Comparative Example 4 Comparative Example 5 Electromagnetic shielding performance / dB 46.1 54.5 65.3 53.2 66.6
[0074] The test results in Table 2 show that the electromagnetic shielding performance of the cement-based material used for groundwater remediation is basically equivalent to that of reinforced concrete and concrete with conductive fillers. The advantages of the cement-based material provided by the present invention are that on the one hand, it has a large porosity and absorbs more electromagnetic waves and reflects more internally; on the other hand, after being used for groundwater remediation, a large amount of heavy metal ions and pollutants are distributed in the pores, surface and interior of the cement-based material, which can act as conductive fillers. The surface morphology of the cement-based material before and after adsorption is shown in Figure 2. Figure 2 At the same time, the internal pore morphology of the cement-based material prepared by high-strength ceramsite was observed under an optical microscope. It can be seen that a large amount of heavy metal ions adhered and solidified in the pores, which will be beneficial to improving the electromagnetic shielding performance of the cement-based material. Figure 3 shown.
[0075] In summary, the cement-based material provided by the present invention has good mechanical properties and can be used as an electromagnetic shielding material after being used for groundwater remediation, and its electromagnetic shielding effect is excellent.
[0076] The above embodiments are merely examples for clarification and are not intended to limit the implementation methods. Those skilled in the art will appreciate that other variations or modifications may be made based on the above descriptions. It is not necessary and impossible to enumerate all implementation methods here, and any obvious variations or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for recycling cement-based materials after groundwater remediation in the field of electromagnetic shielding, characterized in that: The following steps are involved: S1. Mixing and stirring the silica-alumina material, aggregate, and ferrite magnetic powder for 30 seconds to 1 minute, adding an additive, and continuing stirring for 30 seconds to 1 minute to obtain a mixture. The mixture is placed in a mold, compacted, and sealed. The mold is removed after 1 day, and then cured under standard curing conditions for 28 days to obtain a cement-based material. S2. The cement-based material prepared in step S1 is buried around groundwater containing heavy metal ions, the groundwater is purified for 1-2 years, and then taken out and used as an electromagnetic shielding material.
2. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 1, characterized in that: In step S1, the silicon-aluminum material is 100 parts, the aggregate is 150-640 parts, the ferrite magnetic powder is 2-10 parts, and the additive is 20-85 parts.
3. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 1, characterized in that: The silica-alumina material includes: 70-80wt% of conventional silica-alumina raw materials and 20-30wt% of silica-alumina raw materials with high iron oxide content; the conventional silica-alumina raw materials are one or more of cement, mineral powder, silica fume, and metakaolin; the silica-alumina raw materials with high iron oxide content are one or more of steel slag, iron tailings, red mud, and coal gasification slag.
4. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 1, characterized in that: The ferrite magnetic powder is mainly composed of iron oxide or ferroferric oxide, has a purity greater than 99.9%, and a particle size of 0.06 to 0.6 mm.
5. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 1, characterized in that: The aggregate is one or more of crushed stone, recycled brick-concrete material, and high-strength ceramsite.
6. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 1, characterized in that: The auxiliary agent is water or an alkaline activator; when the silicon-aluminum raw material contains one or more of mineral powder, high-alkaline ore, and steel slag, the auxiliary agent is an alkaline activator.
7. The method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to claim 6, characterized in that: The preparation method of the alkaline activator comprises the following steps: adding an alkali into water, stirring and dissolving the alkali, then adding a silicate thereto, and continuing stirring for 30 seconds to 2 minutes to prepare the alkaline activator; wherein the mass ratio of the alkali, water, and silicate is 1:(3-4):(1.5-2.5); the alkali is one of sodium hydroxide and potassium hydroxide, or a mixture thereof; and the silicate is one of sodium silicate and potassium silicate, or a mixture thereof.
8. A cement-based material prepared by the method for recycling cement-based materials used for groundwater remediation in the field of electromagnetic shielding according to any one of claims 1 to 7.
9. The cement-based material according to claim 8 is used as a material for making electromagnetic shielding room walls, shielding doors or shielding boxes after being used for groundwater remediation.
Citation Information
Patent Citations
Red mud / steel slag-based wave-absorbing cementing material and preparation method thereof
CN112876185A
Composite wave-absorbing material based on fly ash as well as preparation method and application of composite wave-absorbing material
CN116693275A